PENGARUH UKURAN PERUSAHAAN, KINERJA KEUANGAN, TIPE INDUSTRI, DAN FINANCIAL LEVERAGE TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY: STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2011-2013 - Mandaika, Yusi; Salim, Hasan (Universitas Katolik Indonesia Atma Jaya, 2015)
The purposes of this research is to know the impact of size of company, financial performance, type of industry, and financial leverage toward Corporate Social Responsibility (CSR) disclosure. Sample of this research is manufacturing companies that are registered at Indonesian Stock Exchange during 2011 until 2013. Based on research, the conclusion is only one variable which influenced significantly toward CSR disclosure, the variable is type of industry. Meanwhile other three variables that is company size, financial performance, and financial leverage is proven have no any influence toward CSR disclosure.